The Reality of Disappearance: : Critical Theory and Extinction - Crawford, Ryan (Cosmos and History: The Journal of Natural and Social Philosophy, 2022)
Debates about the planet’s recent entrance into an epoch of earth history now characterized by the destructive effects of humankind’s having become a planetary force to rival plate tectonics, supervolcanos and asteroid impacts should have the effect of placing Theodor W. Adorno and Walter Benjamin’s conception of natural history in a new light. For what it is perhaps most striking about this conception is not only its proximity to a present made newly aware of nature and history’s total interpenetration, but just how precisely its understanding of natural history’s essential transitoriness accords with what is now everywhere observable: that ever-accelerating process of disintegration through which it becomes clear that the life of phenomena can only be known today if it is also known in terms of that reality of disappearance to which the current age daily testifies. For Adorno and Benjamin, such a conception of natural history had very real consequences for how philosophical cognition and construction would have to be remade, leading both to pursue far-reaching experiments in intellectual production that it is the task of this paper to reconstruct in the light of its possible relevance for the theory and practice of critical theory today. To draw out the stakes of these experiments will first require a reconsideration of current efforts at contending with some of the most practical problems of our own present. Setting out from Alexander Kluge’s demonstration that the kind of “learning processes” necessary for effective resistance often fail because they are simply far slower than the combined force and velocity achieved by prevailing systems of domination, exploitation and extraction, this paper will then ask how a critical theory informed by natural history might today confront the contemporary problem of tactics and strategies at a time when the forces of organized destruction have themselves changed so dramatically. For now that older, more traditional systems of coercion have long since given way to a novel system of overwhelming planetary exploitation, extraction and extermination, it is necessary to ask again how such transformations in the forms of organized violence might be met by corresponding transformations in the theory and practice of critical theory in this new time of extinction. In response, this paper will seek to reconstruct the history of debates in critical theory about theory and praxis, tactics and strategies in the light of more recent discussions about how to combat a system whose result is the continuing and exponential increase in destruction brought about by global warming. The paper will then conclude by setting Adorno and Benjamin’s conception of natural history in relation to more systematic conceptions of contemporary society by turning to those writers, like Wolfgang Streeck and Andreas Malm, who have recently begun to consider how the many contradictions and forces of destruction inbuilt to present-day society may well require a fundamental reconsideration of the contemporary status of various inherited forms of political resistance.